Providing Epistemic Support for Assessments Through Mobile-Supported Sharing Activities. Issue 4 (1st October 2016) - Raclaw, Joshua; Robles, Jessica S.; DiDomenico, Stephen M.
ABSTRACT: This article examines how participants in face-to-face conversation employ mobile phones as a resource for social action. We focus on what we call mobile-supported sharing activities, in which participants use a mobile phone to share text or images with others by voicing text aloud from their mobile or providing others with visual access to the device's display screen. Drawing from naturalistic video recordings, we focus on how mobile-supported sharing activities invite assessments by providing access to an object that is not locally accessible to the participants. Such practices make relevant coparticipants' assessment of these objects and allow for different forms of coparticipation across sequence types. We additionally examine how the organization of assessments during these sharing activities displays sensitivity to preference structure. The analysis illustrates the relevance of embodiment, local objects, and new communicative technologies to the production of action in copresent interaction. Data are in American English.